MASA DEPAN PENGEMBANGAN USAHA KECIL DAN MENENGAH (UKM): PERSPEKTIF JARINGAN PERUSAHAAN DAN KEBIJAKAN - Mumuh Muksin (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
We review policies that support SMEs in various fields. Our review shows that opinions suggesting that subsidizing SME activities (different from some company activities regardless of size) is not economically justified. Nonetheless, it is widely recognized that SMEs suffer relative losses to large companies, especially in the area of ​​access to information and technology. We then study the possibilities offered by the network in helping SMEs deal with the losses they experience. Our research shows that there are benefits to companies from participating in networks. Furthermore, because networks can help companies overcome some of their innate losses, they can become independent of public assistance and be better able to compete with larger companies once initial impetus is given for the establishment of cooperative networks that can enable companies to compete more effectively.